Ficus benghalensis as Potential Inhibitor of 5α-Reductase for Hair Growth Promotion: In Vitro, In Silico, and In Vivo Evaluation - Jawaria Iltaf; Sobia Noreen; Muhammad Fayyaz ur Rehman; Shazia Akram Ghumman; Fozia Batool; Muhammad Mehdi; Sara Hasan; Bushra Ijaz; Muhammad Safwan Akram; Haider Butt (Frontiers Media S.A., 2021)
The screening of hair follicles, dermal papilla cells, and keratinocytes through in vitro, in vivo, and histology has previously been reported to combat alopecia. Ficus benghalensis has been used conventionally to cure skin and hair disorders, although its effect on 5α-reductase II is still unknown. Currently, we aim to analyze the phytotherapeutic impact of F. benghalensis leaf extracts (FBLEs) for promoting hair growth in rabbits along with in vitro inhibition of the steroid isozyme 5α-reductase II. The inhibition of 5α-reductase II by FBLEs was assessed by RP-HPLC, using the NADPH cofactor as the reaction initiator and Minoxin (5%) as a positive control. In silico studies were performed using AutoDock Vina to visualize the interaction between 5α-reductase II and the reported phytoconstituents present in FBLEs. Hair growth in female albino rabbits was investigated by applying an oral dose of the FBLE formulation and control drug to the skin once a day. The skin tissues were examined by histology to see hair follicles. Further, FAAS, FTIR, and antioxidants were performed to check the trace elements and secondary metabolites in the FBLEs. The results of RP-HPLC and the binding energies showed that FBLEs reduced the catalytic activity of 5α-reductase II and improved cell proliferation in rabbits. The statistical analysis (p < 0.05 or 0.01) and percentage inhibition (>70%) suggested that hydroalcoholic FBLE has more potential in increasing hair growth by elongating hair follicle's anagen phase. FAAS, FTIR, and antioxidant experiments revealed sufficient concentrations of Zn, Cu, K, and Fe, together with the presence of polyphenols and scavenging activity in FBLE. Overall, we found that FBLEs are potent in stimulating hair follicle maturation by reducing the 5α-reductase II action, so they may serve as a principal choice in de novo drug designing to treat hair loss.